Acute decompensated pulmonary hypertension. (15th November 2017) - Savale, Laurent; Weatherald, Jason; Jaïs, Xavier; Vuillard, Constance; Boucly, Athénaïs; Jevnikar, Mitja; Montani, David; Mercier, Olaf; Simonneau, Gerald; Fadel, Elie; Sitbon, Olivier; Humbert, Marc
Acute right heart failure in chronic precapillary pulmonary hypertension is characterised by a rapidly progressive syndrome with systemic congestion resulting from impaired right ventricular filling and/or reduced right ventricular flow output. This clinical picture results from an imbalance between the afterload imposed on the right ventricle and its adaptation capacity. Acute decompensated pulmonary hypertension is associated with a very poor prognosis in the short term. Despite its major impact on survival, its optimal management remains very challenging for specialised centres, without specific recommendations. Identification of trigger factors, optimisation of fluid volume and pharmacological support to improve right ventricular function and perfusion pressure are the main therapeutic areas to consider in order to improve clinical condition. At the same time, specific management of pulmonary hypertension according to the aetiology is mandatory to reduce right ventricular afterload. Over the past decade, the development of extracorporeal life support in refractory right heart failure combined with urgent transplantation has probably contributed to a significant improvement in survival for selected patients. However, there remains a considerable need for further research in this field. Acute decompensated PH is a life-threatening condition requiring specific management in a specialised centre http://ow.ly/non530fkhmA